Relative age effect in Olympic Judo athletes: A weight category analysis - Albuquerque, M. R.; Tavares, V.; Lage, G. M.; de Paula, J. J.; da Costa, I. T.; Malloy-Diniz, L. F. (Science & Sports, 2013)
Introduction: In the relative age effect (RAE) literature, several papers have shown differences in the relative effect of age on different play positions; however, combat sports, such as Olympic Judo, use weight categories. Objective: This study aimed to investigate the RAE in different weight categories of judo athletes. Methods and subjects: The study sample consisted of 1738 athletes who had competed in the Olympic Games. Results: The present study showed that the RAE occurs in heavy athletes. Conclusion: In conclusion, the RAE in combat sports, such as Olympic Judo, needs to be investigated in separate weight categories for a better analysis of the results.